Behavioral and molecular bases of the anthelmintic activity of essential oils explored in the nematode Caenorhabditis elegans - Hernando, Guillermina Silvana (2021)
Control of helminth infections in both human and veterinary med icine currently relies mainly on chemotherapy, but acquisition of resistance is an increasing problem that leads to the urgent need of discovery of novel drugs. C. elegans has demonstrated to be a model system for the discovery of new anthelmintics and for char acterizing their mechanisms of action and resistance. Essential oils (EOs) are natural products produced by aromatic plants. We per form paralysis assays of wild-type and mutant C. elegans strain to identify EOs with potential anthelmintic activities, reveal the active components, their target sites, and mechanisms of action. We found that EOs belonging to different orders produce rapid paralysis of C. elegans with EC50 values between 0.02-2 % EOs. All EOs test ed also inhibited egg hatching, a property related to anthelmintic ability. Thus, EOs mediate both rapid and long-term anthelmintic effects. We examined anthelmintic properties of terpenoids and phenylpropenes and determined that all compounds tested produce both paralysis and egg-hatching inhibition. By testing mutant worms, we identified the muscle L-AChR and GABA receptors as EOs and trans-cinnamaldehyde (TC, phenylpropene) targets. Thus, by modulating two receptors with key roles in worm motility, these EOs emerge as novel sources of anthelmintic compounds. To unequivo cally confirm that these receptors are targets of TC and to describe the mechanism by which they affect these receptors, we performed whole-cell and single-channel recordings from C. elegans muscle cells. Electrophysiological recordings at the single-channel level re vealed that TC reduces L-AChR channel activity without affecting channel properties. The results are compatible with the action of these drugs as allosteric inhibitors. It is hoped that this work can update the recent progress on natural nematicide discoveries and provide new ideas for the design and mechanism of action studies of anthelmintics.